Recovering Assemblages Unfolding Sociomaterial Relations of Drug Use and Recovery - Sultan, Aysel (Singapore : Springer Nature Singapore : Imprint: Palgrave Macmillan, 2022)
Drawing together insights and provocations from diverse fields of inquiry, this important new book asks probing questions about the lived experience of substance use and misuse, health and recovery. What if we were to approach these experiences in terms of spaces and events, affects and relations rather than subjects and their settled identities? In charting this course, the book offers a powerful new social logic of health, wellbeing and recovery. - Cameron Duff, Associate Professor, RMIT University This is an important book which expands and deepens our understanding of recovery. It presents recovery as something made in practice, taking multiple forms in specific contexts. Drawing on qualitative research with young people in Azerbaijan and Germany, Sultan takes the concept of recovery beyond its more familiar and normative iterations and instead introduces the reader to a fascinating field of dynamic and unruly relations. - Helen Keane, Professor in Research School of Social Sciences, Australian National University Recovering Assemblages offers an exciting new insight into the policies and practices of recovery and drug use bridging critical drug studies and the sociology of health and illness. The book investigates lived experiences of young people in Azerbaijan and Germany during their personal recovery from alcohol and other drug use and shows the contingency of real experiences. The sociomaterial and ontological analyses unfold the interrelation of practices, spaces, bodies, and affects in experiencing recovery both within and outside of various treatment facilities. The book will appeal to a range of scholars, postgraduates, and undergraduates engaged in critical, methodological, and empirical studies of recovery, drug use, and policy. Aysel Sultan is a researcher at the Department of Science, Technology and Society, Technical University of Munich and co-Editor-in-Chief of the quarterly Drugs, Habits and Social Policy journal. .
Part 1: Connecting the Dots -- 1. The need to rethink 'recovery' -- 2. Materialist Thinking in Critical Recovery Studies -- 3. The stake of a comparative approach -- 4. Constructing stories, rebuilding attachments -- Part 2: Diversifying Knowledge and Science of Recovery -- 5. Assembling and Diversifying Social Contexts of Recovery -- 6. Tracing Relations and Unfolding Recovery Forms -- 7. Body, Detox, Affect -- 8. Enacting Recovery: Process or Endpoint? -- Part 3: Recovery From and Within Drug Use.
Keywords: Social medicine; Science-Social aspects; Public health; Medical Sociology; Science and Technology Studies; Public Health